THE ASSESSMENT OF THE INCIDENCE OF SKIN DISORDERS IN RUSSIAN FEDERATION IN 2003-2016 - A. A. Kubanova; A. A. Kubanov; L. E. Melekhina; E. V. Bogdanova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The paper presents the analysis of the incidence and prevalence of skin disorders in general and of some skin diseases in Russian Federation in 2003-2016. Age-specific and federal district-specific profile of prevalence and incidence rates is also present.